Penerapan Analisis Swot pada Pasar Offline yang Menurun Akibat Pasar Online - Tyo Rizky Siagian; Henni Setiani; Kayla Nina Afrina; Nurbaiti Nurbaiti (Trending: Jurnal Manajemen dan Ekonomi, 2024)
The internet has become one of the technologies most frequently used by society today. E-commerce users in Indonesia are expected to continue to increase, as can be seen from the graphic visualization results. In semester 1 of 2020, 63.6% of the total Indonesian people shopped online, while in semester 2 of 2020 there was an increase of 69.1%. Therefore, it can be concluded that this pandemic has a big meaning and is even able to accelerate buying and selling transactions from offline to online until now. However, the Deputy Minister of Trade of the Republic of Indonesia actually said that social media must be removed from the market. This research uses a qualitative approach. The qualitative approach is a research method that focuses its discussion on general principles. By applying a SWOT analysis to the decline in offline market sales due to the rise of the online market, we can identify and analyze the decline in sales in the offline market. Traders in traditional and modern markets in various regions still complain that the number of visitors continues to decline. The trigger was not only caused by the increase in prices of various basic commodities, but also the presence of online markets which is thought to have caused a decline in people's purchasing power.